INTEGRATED STRATEGY FOR THE RECOVERY OF URBAN RIVER SECTIONS. THE CASE OF THE RIVER PILES IN GIJÓN COMPATIBLE WITH SPORTING USES. - Pellicer Corellano, Francisco; Barrao Simorte, Samuel; López-Álvarez, Marcos (Geographicalia, 2021)
The environmental recovery of the river Piles as it passes through Gijón, with the compatible inclusion of nautical sporting uses, represents an important challenge for the city. Gijón city council has drawn up an Action Plan that proposes the demolition of the dam that facilitates the practice of sports in the navigable ring. The municipal decision has unleashed strong social opposition led by the Real Grupo Cultural Covadonga (RGCC), which sees the practice of canoeing in danger. The conflict is giving rise to an interesting debate on the always controversial management of river areas in the city. The scientific studies that support the political decision of the Gijón City Council have a markedly sectorial character and therefore do not offer an integrated vision of the problem in which environmental, social, economic and cultural elements and factors of the urban-river interface interact. In this context, the holistic approach of Geography with the highly specialised contributions of Biology in an interdisciplinary dialogue, offers an appropriate conceptual and methodological framework for integrated strategic planning, and is aligned with the advanced policies of the EU and Spain.